Faculty Bibliography - Clarie, Thomas C.; Koch, Róbert; Yacher, Leon I.; Sandomirsky, LNatalie (Southern Connecticut State University, 1978)
Keywords: Bibliography; Faculty; Southern Connecticut State University; dept.art; dept.egm; dept.lib; faculty_collection

Working Bibliography of Owls of the World: With Summaries of Current Taxonomy and Distributional Status - Clark, Richard J.; Smith, Dwight G.; Kelso, Leon H. (National Wildlife Federation scientific & technical series ; no. 1, 1978)
Keywords: Bibliography; Owls; dept.egm; faculty_collection

The Association of American Geographers, the First Seventy-Five Years, 1904-1979 - James, Preston E.; Martin, Geoffrey J. (The Association, 1978)
Keywords: Association of American Geographers; dept.egm; faculty_collection

Marriage Migration and Racial Mixing in Colonial Tlazazalca, (michoacán, Mexico), 1750-1800 - Yacher, Leon I. (Discussion paper series (Syracuse University. Department of Geography) ; no. 32, 1977)
Keywords: Case studies; Case studies; Endogamy and exogamy; Marriage; Mexico; Tlazazalca (Michoacán); dept.egm; faculty_collection

Man and the Earth. - Hoyt, Joseph Bixby (Prentice-Hall, 1973)
Keywords: Human ecology; Geography; dept.egm; faculty_collection

Ellsworth Huntington; His Life and Thought, - Martin, Geoffrey J. (Archon Books, 1973)
Keywords: Huntington, Ellsworth, 1876-1947; SCSU Faculty Scholar Award; award_winner; dept.egm; faculty_collection

Access to the Sea for Developing Land-Locked States. - Glassner, Martin Ira (Nijhoff, 1970)
Keywords: Access to the sea (International law); Landlocked states; Developing countries; Commerce; award_winner; dept.egm; faculty_collection

How Connecticut pediatricians view polluted air - Kane, D.N. (Connecticut Medicine, 1978)
Keywords: Air Pollution; Attitude of Health Personnel; Connecticut; Pediatrics; air pollution; dept.egm; editorial; ⛔ No DOI found

Changing Jamaica - Kuper,a - Glassner, M (Professional Geographer, 1978)
Keywords: dept.egm; ⛔ No DOI found

Legal Framework of Unctad in World-Trade - Koul,ak - Glassner, MI (Journal of Developing Areas, 1978)
Keywords: dept.egm; ⛔ No DOI found

Transit Rights for Land-Locked States and Special Case of Nepal - Glassner, MI (World Affairs, 1978)
Keywords: dept.egm; ⛔ No DOI found

Geographer Among Diplomats - Glassner, MI (Geographical Review, 1977)
Keywords: dept.egm

Land-Locked Nations and Development - Glassner, MI (International Development Review, 1977)
Keywords: dept.egm; ⛔ No DOI found

Latin-America and Development of Law of Sea .1. Regional Documents, National Legislation - Szekely,a - Glassner, MI (Journal of Developing Areas, 1977)
Keywords: dept.egm; ⛔ No DOI found

New Era of Ocean Politics - Hollick,al and Osgood,re - Glassner, M (Professional Geographer, 1976)
Keywords: dept.egm; ⛔ No DOI found

Law of Sea - Caracas and Beyond - Proceedings of 9th Annual Conference of Law-of-Sea-Institute - Christy,ft, Clingan,ta, Gamble,jk, Knight,hg and Miles,e - Glassner, MI (Professional Geographer, 1976)
Keywords: dept.egm; ⛔ No DOI found

Introduction to Physical-Geography - Gabler,re, Sager,r, Brazier,s and Pourciau,j - Sakalowsky, PP (Professional Geographer, 1976)
Keywords: dept.egm; ⛔ No DOI found

Physical-Geography Today - Portrait of a Planet - Sakalowsky, PP (Professional Geographer, 1976)
Keywords: dept.egm; ⛔ No DOI found

Beach morphology and nearshore processes on a sheltered beach — The case of Napatree Beach, Rhode Island - Sakalowsky, Peter P. (Marine Geology, 1975)
On the north side of Napatree Beach, short-term changes of the beach-face within the intertidal zone were studied to determine those processes most influential in causing change where nearshore processes are low in magnitude and beach changes are subtle. The data were subjected to multiple linear correlation and stepwise multiple-regression analyses. Tide level accounts for 41% of the explained variation for the relationship between the processes and beach height. Tide level is the only significant element effecting change in the beach profile. Wave height has no influence on changes in beach morphology. Significant results of beach energy associations have been obtained where low-amplitude nearshore processes are present even when beach changes are subtle. © 1975.
Keywords: dept.egm

Maritime Law-Enforcement - Maritime Sovereignty and Continental-Shelf of Venezuela Within International Context of Maritime Law - Spanish - Nweihed,kg - Glassner, MI (Journal of Developing Areas, 1975)
Keywords: dept.egm; ⛔ No DOI found

Climatology - Fundamentals and Applications - Mather,jr - Sakalowsky, PP (Professional Geographer, 1975)
Keywords: dept.egm; ⛔ No DOI found

Israel's maritime boundaries - Glassner, Martin Ira; Unger, Michael (Ocean Development and International Law, 1974)
While land boundaries have occupied the attention of Israelis since 1948 and even earlier, they have been little concerned with the sea, and the legislation concerning their maritime boundaries is vague and incomplete. In addition, since the Six Day War Israel occupies territory with several different territorial seas, resulting in a quite complex ad hoc situation. The sea is becoming more important to Israel and she is gradually turning her attention more and more to maritime matters. It would be well if an orderly system of maritime boundaries and cooperation in utilizing the resources of the sea could be arranged with her neighbors, but that seems impossible for the forseeable future. It does seem likely, however, that in connection with or shortly after the forthcoming Law of the Sea Conference, Israel will as a minimum extend her territorial sea from six miles to twelve, while stoutly maintaining the right of free transit through international straits. © 1974 Taylor & Francis Group, LLC.
Keywords: dept.egm

Bedouin of Southern Sinai Under Israeli Administration - Glassner, MI (Geographical Review, 1974)
Keywords: dept.egm

Law of Sea - Research on Maritime Sovereignty and Continental Shelf of Venezuela in Realm of International Law of Sea - Nweihed,kg - Glassner, MI (Annals of the Association of American Geographers, 1974)
Keywords: dept.egm; ⛔ No DOI found

Population Figures for Mandan Indians - Glassner, MI (Indian Historian, 1974)
Keywords: dept.egm; ⛔ No DOI found

Modifying Weather - Social Assessment - Sewell,wrd - Sakalowsky, PP (Professional Geographer, 1974)
Keywords: dept.egm; ⛔ No DOI found

Robert lemoyne barrett, 1871–1969; last of the founding members of the association of american geographers1 - Martin, Geoffrey J (The Professional Geographer, 1972)
Keywords: dept.egm

Nationalism in Early American Geographies: 1784-1845 - Antonelli, Michael F. (Journal of Geography, 1970)
There existed clear demonstrations of nationalism in geography textbooks written by Americans during two significant epochs in the history of the United States. Geographies regarded the environment, people or institutions of the United States either with extreme adulation or subtle pride. They viewed the nation favorably when its strengths and weaknesses were compared to each other or to foreign elements, even when objective evidence did not support such an assessment. And, finally, they reached a host of young and impressionable Americans, and instilled in them a fervor for their country. © 1970 Taylor and Francis Group, LLC.
Keywords: dept.egm

Chibchas - History and Re-Evaluation - Glassner, M (Americas, 1970)
Keywords: dept.egm

Foreign Relations of Jamaica and Trinidad and Tobago, 1960-1965 - Glassner, MI (Caribbean Studies, 1970)
Keywords: dept.egm; ⛔ No DOI found

Rio-Lauca - Dispute Over an International River - Glassner, MI (Geographical Review, 1970)
Keywords: dept.egm

ON AAG history - James, Preston E; Martin, Geoffrey J (The Professional Geographer, 1979)
The seventy-fifth anniversary of the Association of American Geographers is a time to celebrate. To set the tone for the anniversary meetings in Philadelphia, I asked Geoffrey Martin, Marvin Mikesell, and John Adams to discuss significant events in the AAG's past, the Association’s present state, and prospects for the future. Their presentations were made in the initial session of the meetings on Sunday evening, April 22. We are pleased to reproduce for the members of the Association the transcripts of those verbal presentations. We are indebted to each of these colleagues for the excellent start they provided for our largest-ever professional meeting.—Brian J. L. Berry, President. © 1979 by the Association of American Geographers.
Keywords: dept.egm

Review: Climate and Human Ecology. Jim Norwine, ed. - Yacher, Leon (Professional Geographer, 1979)
Keywords: dept.egm

Geographies of Mind - Essays in Historical Geosophy (in Honor of Wright,jk) - Lowenthal,d and Bowden,mj - Martin, GJ (Professional Geographer, 1976)
Keywords: dept.egm; ⛔ No DOI found

History of Study of Landforms or Development of Geomorphology - .2. Life and Work of Davis,wm - Chorley,rj, Beckinsale,rp and Dunn,a - Martin, GJ (Professional Geographer, 1974)
Keywords: dept.egm; ⛔ No DOI found